Identification of influential factors in oral communication competence of the English learning in students - Barrios, Javier Arturo; Llinas Torres, Jhony Rafael (Revista Cedotic, 2018)
Speaking is an important skill that needs to be mastered as it is the best way to communicate with other people in order to deliver opinions and express ideas, but the fact is that secondary school students’ ability in speaking English is very low in Colombia. This research intends to determine the factors that affect development of oral communication competence within a group of ninth graders at an official Institution in the Colombian Caribbean Coast. The main objectives of this study are to investigate the most frequently factors that influence the development of oral communication competence, and to describe the most frequent problems faced by students and teachers when developing effective oral communication competence in English. This study is a kind of exploratory case. For data-collection were used interviews, observation and a survey about students’ opinions. The findings of this study showed four categories that were defined: motivation, exposure, authentic and funny material and classroom atmosphere. And among the factors that could have a positive effect on students' oral production, several categories were identified: attracting material, scaffolding, funny activities, disposition, and teacher´s methodology... The result of this study provides useful insights for English language teachers in teaching speaking.